Rapid maxillary canine retraction by dental distraction: A clinical study - Koteswara Prasad, N. K. (Medknow Publications & Media Pvt Ltd, 2014)
AIM: The aim of this clinical study was to perform rapid maxillary canine retraction through distraction of the periodontal ligament and investigate the rate and amount of canine retraction, amount of anchor loss, the nature of tooth movement achieved, and radiographic changes in the periodontal ligament region during and after canine distraction. MATERIALS AND METHODS: This study was conducted on 10 distractions ranging in age from 14 years to 25 years who needed canine retraction and first premolar extraction in the maxillary arch. Ten canine distractions were carried out with custom-made, tooth-borne intra-oral distraction device. RESULTS: The results indicate that the periodontal ligament can be distracted just like the mid-palatal suture in rapid palatal expansion and the maxillary canines are retracted rapidly into the first premolar extraction space at the rate of about 2.53 mm/week. CONCLUSION: Though this study indicates that the periodontal ligament can be distracted to elicit rapid tooth movement, the long-term effects of canine distraction are not well known and need close monitoring.